1982
DOI: 10.1113/jphysiol.1982.sp014402
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic responses to imposed sinusoidal movement of the human thumb.

Abstract: SUMMARY1. The interphalangeal joint of the thumb was driven through sinusoidal flexionextension movements while electromyograms were recorded from over the flexor pollicis longus muscle.2. When the subject relaxed his thumb the movement generated no detectable e.m.g. response. When, however, he exerted a voluntary flexing force electrical activity could be recorded from the flexor pollicis longus, the amplitude of which was modulated at the frequency of the movement.3. As the driving frequency was increased, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Studies in the cat have shown similar discrete bursts of activity phase-locked to cyclic stretching which became more probable as the amplitude of the stretch increased (Jansen and Rack 1966;Rosenthal et al 1970) and human studies also have shown EMG traces in which such saturation was apparent (e.g. Brown et al 1982b). Brown et al commented on the EMG being "well modulated by movement" (p. 95) in the 5 -15 Hz range.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies in the cat have shown similar discrete bursts of activity phase-locked to cyclic stretching which became more probable as the amplitude of the stretch increased (Jansen and Rack 1966;Rosenthal et al 1970) and human studies also have shown EMG traces in which such saturation was apparent (e.g. Brown et al 1982b). Brown et al commented on the EMG being "well modulated by movement" (p. 95) in the 5 -15 Hz range.…”
Section: Discussionmentioning
confidence: 98%
“…The saturation of the motor neuron modulation occurred at higher frequencies because the gain of the EMG reflex response increases as a power function (exponent > 1) of frequency (Cathers et al 1999) to about 10 Hz (Neilson 1972a,b;Neilson and Neilson 1978;Zahalak and Heyman 1979;Zahalak 1981, 1993;Cathers et al 1999). Beyond 10 Hz, the reflex gain decreases and this may be the result of saturation (Brown et al 1982b;Matthews 1993). …”
Section: Discussionmentioning
confidence: 99%
“…In earlier studies of the wrist flexors with individual ramp-type stretches the delayed response was very greatly reduced on increasing the repetition rate from 041 to 1 Hz (Rothwell, Day, Beradelli & Marsden, 1986). However, that of flexor pollicis longus was much less affected (see also, Brown et al 1982). Conceivably, this betokens yet further subdivisions of the reflex.…”
Section: Wider Implicationsmentioning
confidence: 92%
“…In the monkey, the EMG modulation of the stretch reflex of jaw muscles increases up to 20 Hz, and no peculiarities were commented upon for frequencies up to 50 Hz (Goodwin, Hoffman & Luschei, 1978). The response of the human flexor pollicis longus tends to decrease above 12 Hz (Brown, Rack & Ross, 1982), while that of triceps surae does not so obviously do so (Agarwal & Gottlieb, 1977;Evans et al 1983). A point of possible significance is that in some of these experiments there was little tonic EMG activity between the phasic EMG bursts elicited by the stretching; in effect, a series of semi-isolated excitatory responses were being studied.…”
Section: Relation To Previous Gross Emg Recordingsmentioning
confidence: 99%
“…Electromyograms were recorded from over the surface of flexor pollicis longus (see Brown et al 1982b). Force, position and e.m.g.…”
Section: Methodsmentioning
confidence: 99%